2018
DOI: 10.1364/ol.43.002716
|View full text |Cite
|
Sign up to set email alerts
|

Multimode four-wave mixing with a spatially structured pump

Abstract: We demonstrate, to the best of our knowledge, a new four-wave mixing geometry based on structured light. By utilizing near-field diffraction through a narrow slit, the pump beam is asymmetrically structured to modify the phase-matching condition, generating multimode output in both the spatial and frequency domains. We show that the frequency parameter enables selection of various spatial-mode outputs, including a twin-beam geometry, which preserves relative intensity squeezing shared between the two beams. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The idea exploited the simultaneous fulfillment of two phase matching conditions that reinforce one another. Using a long medium approximation, radial and angular mode conversion by FWM in a heated Rb vapour was demonstrated, making evident the role of the Gouy phase-matching in this regime 170 . Beyond just spatial DoFs, the spatial and temporal DoFs are not independent in this process 171 , where frequency control enables selection of various spatial modes as outputs.…”
Section: Four-wave Mixingmentioning
confidence: 94%
“…The idea exploited the simultaneous fulfillment of two phase matching conditions that reinforce one another. Using a long medium approximation, radial and angular mode conversion by FWM in a heated Rb vapour was demonstrated, making evident the role of the Gouy phase-matching in this regime 170 . Beyond just spatial DoFs, the spatial and temporal DoFs are not independent in this process 171 , where frequency control enables selection of various spatial modes as outputs.…”
Section: Four-wave Mixingmentioning
confidence: 94%
“…In addition to using a SLM to adjust the angle between two pump beams, Swaim et al also proposed a new FWM geometry with a structured pump, which is generated by using near-field diffraction through a slit [141] . As shown in Fig.…”
Section: Spatially Structured Pump Systemmentioning
confidence: 99%
“…The spatial multiplexing based on cascaded FWM in the previous subsection shares one pump beam for generating two independent FWM processes. At the same time, Wang et al [137] , Zhang et al [138] , Liu et al [139,140] , Swaim et al [141] , and Knutson et al [142] also demonstrated the spatially multiplexed FWM process in an atomic vapor cell by utilizing a spatially structured pump. This subsection focuses on generating spatially separated six, ten, and fourteen quantum correlated beams, as well as four bright beams in this way.…”
Section: Optical Quantum States Based On Four-wave Mixing Process In ...mentioning
confidence: 99%
“…Multimode quantum states (MQS) are considered as an essential resource for a fundamental test of quantum physics, [ 25–28 ] and have attracted considerable attention. [ 29,30 ] The reliable methods based on the FWM process for generating MQS have been theoretically proved and experimentally implemented in the different kinds of systems.…”
Section: Introductionmentioning
confidence: 99%